A Cultural Portrait of “little c” Themes in an English Textbook Used by Indonesian Junior High School Students: A Content Analysis - Lintang Indah Ayu Respati Dewi (Aksara: Jurnal Bahasa dan Sastra, 2019)
In recent decades, cultural content analysis of EFL textbooks has received a wide attention in ELT pedagogy. This research aims at analyzing the cultural themes, especially “little c” and culture categories presented in an English textbook used by Junior High School students in Indonesia. This study was carried out using Xiao’s suggested themes for detecting “little c” that represent food, holiday, lifestyles, customs, values, hobbies, and gesture/body language. Besides, it also investigated the culture categories proposed by Cortazzi and Jin, namely source culture, target culture, and international culture. The result showed that the presentation of the source, target, and international culture are in an imbalance proportion. The textbook’s content mostly exposes target culture and source culture. Meanwhile, international culture was not exposed. Moreover, value and food dominated the cultural theme in the textbook. Meanwhile, lifestyle and customs are less exposed. Furthermore, three themes of “little c” (holiday, hobbies, and gestures) were not exposed at all. Due to the imbalance proportion of cultural content, the textbook developers should provide a more balanced proportion of cultural contents in terms of themes and categories to help learners gain more knowledge related to intercultural understanding. http://dx.doi.org/10.23960/aksara/v20i2.pp88-100